Pendapatan Usahatani Pola Mix Cropping Tanaman Cabai Rawit Dan Tomat Di Desa Tumaratas II Kecamatan Langowan Barat Kabupaten Minahasa - Sekeon, Olivia M.; Rengkung, Leonardus Ricky; Tarore, Melissa Lady Gisela (Sam Ratulangi University, 2024)
This study aims to determine the income of cayenne pepper and tomato farming using mixed cropping patterns in Tumaratas II Village, Langowan Barat District, Minahasa Regency. The research was conducted from July to September 2023. The research location was Tumaratas II Village, West Langowan District, Minahasa Regency. The data collection method used in this research is primary data obtained using direct interview techniques with respondents, using a questionnaire as a tool in data collection, while secondary data is obtained from data that is already available from village documents, sub-district offices and other related sources for research purposes. The sampling method used purposive sampling method. The population studied in this study were farmers who grew mixed crops of cayenne pepper and tomatoes. The data analysis method was carried out using quantitative methods and the research results were presented in tabular form. Knowing the total revenue in one crop period is determined using the revenue and income formula. Based on the results of the research conducted, it is concluded that each farmer respondent has a different average so that the income earned is also very different. The total income received in mixed crop farming amounted to IDR395,355,682.28. The largest income in mixed crop farming is IDR77,521,932.00, while the smallest income is IDR3,276,800.00.